Analysis of JNE 093 Pulo Gebang Indah Service Quality Using Servqual Dimensions and Importance Performance Analysis - Muhammad Abigail Athallah; Sonny Rustiadi (UNIVED Press, 2026)
This research aims to evaluate customer perceptions and expectations of JNE 093 Pulo Gebang Indah service quality and provide recommendations for improvement in its service quality. This research uses a mixed method by first conducting quantitative research using surveys with Likert scale answers for service quality questionnaires and distribute it to customers. The sample size for surveys is 100 respondents from JNE 093 Pulo Gebang Indah’s customers. Subsequently, qualitative research is conducted using surveys with an open-ended question for customers and semi-structured interviews with the owner and the expert. The results show that customers generally have a positive perception and expectation of the service quality at JNE 093 Pulo Gebang Indah. However, several service indicators have negative gaps. The gaps show that the service perceived by customers does not fully match the level of service expected. This gap provides an important basis for identifying the first quadrant of IPA matrix and at the same time formulate recommendations. This research contributes to the study of service quality in entrepreneurship.